(untitled) (Baghdad Science Journal, 2008)
Films of CdSe have been prepared by evaporation technique with thickness 1µm. Doping with Cu was achieved using annealing under argon atmosphere . The Structure properties of these films are investigated by X-ray diffraction analysis. The effect of Cu doping on the orientation , relative intensity, grain size and the lattice constant has been studied. The pure CdSe films have been found consist of amorphous structure with very small peak at (002) plane. The films were polycrystalline for doped CdSe with (1&2wt%) Cu contents and with lattice constant (a=3.741,c=7.096)A°, and it has better crystallinty as the Cu contents increased to (3&5wt%) Cu. The reflections from [(002), (102). (110), (112), and (201)]planes are more prominent referring to hexagonal unit cell. Therefore the crystal structure of CdSe:Cu films are hexagonal at Cu content (pure, 1&2wt%) with a sharpness and also in the hexagonal form at (3&5wt%).The crystalline size were found to depend on concentration of doping materials, and it is varied between (20.3-81.4)nm and increased with Cu content.